PENTAHELIX APPROACH FOR ACHIEVING INTEGRATED AND SUSTAINABLE TOURISM DEVELOPMENT - Rindang Alfiah; Cindy Monica Febrian; Ratih Novi Listyawati; RR Dewi Junita Koesoemawati (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This research focuses on Sumbermujur Village in Lumajang Regency, Indonesia, which possesses significant potential for natural, man made, and cultural tourism. The research aims to explore the implementation of the pentahelix Model for developing integrated and sustainable tourism. The research is motivated by the challenges of fostering sustainable tourism in rural areas and the need for a collaborative approach that involves key stakeholders, highlighting the urgency of this research. Utilizing the Delphi method, this research engages various stakeholders, including local government, community members, tourism operators, academics, and research institutions, to achieve consensus on a sustainable tourism development model. The research process includes identifying key tourism challenges, designing the pentahelix model through cross-sector collaboration and community involvement, validating the model, and providing policy recommendations. The research results show that in tourism development in Sumbermujur Village, four stakeholders have had cooperative relationships, namely academics, local communities, government, and media. In contrast, private business people involved in tourism have not been involved in the cooperation. To achieve integrated and sustainable tourism development based on the pentahelix model, closer collaboration is needed, especially by involving private businesses. Optimal cooperation between stakeholders in this Penta helix model can positively impact increasing the tourism economy and maximizing the utilization of tourism potential.